Zikir Bordah and Social Relations in the Labuhan Batu Community - Amal, Bakhrul Khair; Suroso, Panji; Ravai, Muhammad; Rambe, Tappil (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This paper aims to collect various types of Bordah recitation that are used in various cultural events in Labuhan Batu during weddings, circumcisions, and gratitude towards God. The meaning is to re-explore the important values of local wisdom in Bordah Zikir that have been lost to answer the challenges of globalization as well as to play an important role in changing social values in Labuhan Batu society. Bordah recitation is an expression of gratitude through beautiful poetry that leads to the divine. This research is very important to explore the values of Bordah's remembrance which have long been forgotten or even lost. This study will greatly support and assist the government's efforts in the mental revolution program which have shown a disorderly direction. The research method that will be used is the socio-anthropological method whose characteristics are "examining informants as research subjects in their daily environment." Researchers and the object under study interact intensely through in-depth observation of the object's life in accordance with the research objectives. This research will be conducted in the Labuhan Batu area which consists of the Malays and Mandailing tribes, North Sumatra.